Prenatal nicotine increases pulmonary α7 nicotinic receptor expression and alters fetal lung development in monkeys - Sekhon, Harmanjatinder S.; Jia, Yibing; Raab, Renee; Kuryatov, Alexander; Pankow, James F.; Whitsett, Jeffrey A.; Lindstrom, Jon; Spindel, Eliot R. (The Journal of Clinical Investigation, 1999)
It is well established that maternal smoking during pregnancy is a leading preventable cause of low birth weight and prematurity. Less appreciated is that maternal smoking during pregnancy is also associated with alterations in pulmonary function at birth and greater incidence of respiratory illnesses after birth. To determine if this is the direct result of nicotine interacting with nicotinic cholinergic receptors (nAChRs) during lung development, rhesus monkeys were treated with 1 mg/kg/day of nicotine from days 26 to 134 of pregnancy. Nicotine administration caused lung hypoplasia and reduced surface complexity of developing alveoli. Immunohistochemistry and in situ α-bungarotoxin (αBGT) binding showed that α7 nAChRs are present in the developing lung in airway epithelial cells, cells surrounding large airways and blood vessels, alveolar type II cells, free alveolar macrophages, and pulmonary neuroendocrine cells (PNEC). As detected both by immunohistochemistry and by αBGT binding, nicotine administration markedly increased α7 receptor subunit expression and binding in the fetal lung. Correlating with areas of increased α7 expression, collagen expression surrounding large airways and vessels was significantly increased. Nicotine also significantly increased numbers of type II cells and neuroendocrine cells in neuroepithelial bodies. These findings demonstrate that nicotine can alter fetal monkey lung development by crossing the placenta to interact directly with nicotinic receptors on non-neuronal cells in the developing lung, and that similar effects likely occur in human infants whose mothers smoke during pregnancy. J. Clin. Invest. 103:637–647 (1999)